PENGARUH PELATIHAN TERHADAP MOTIVASI KERJA DAN KINERJA DI PRAMA SANUR BEACH-BALI - Darmawan, Yuyun Yuniar; Supartha, Wayan Gede; Rahyuda, Agoes Ganesha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
An important objective of the research here is to highlight the impact of staff training on the motivation and performance of the workforce of Hotel Prama Sanur Beach Bali. The number of trainees at the Prama Sanur Beach Bali stands at 59 persons. The sample used in this study is taken from staff working in the Food and Beverage Products, Food and Beverage Service, the Front Office and Housekeeping. A random sample was used to derive the total number of workers surveyed. A partial least squares approach was used for technical analysis used in this research. The result of the research carried out here showed that training has a positive and significant impact not only on worker motivation but also on performance. Training proved to be crucial factor linking motivation and performance of the workers in the sample.
Keywords: training, work motivation, employee performance